PENERAPAN EDUKASI PEMBERIAN CAIRAN (ORALIT) UNTUK MENGATASI DEHIDRASI PADA PASIEN ANAK DENGAN GEDS (GASTROENTRITIS DIARE SEDANG) DI RUANG ANGGREK RS BHAKTI WIRA TAMTAMA SEMARANG - Putri, Rizkyani Awalina; Hastuti, Witri (NHM PRESS, 2024)
Background: Diarrhea is an infectious disease that must be treated immediately. If it is not treated immediately it can cause death, because if treated too late then diarrhea sufferers will lack body fluids (Rendang Indriyani and Putra 2020). According to data (World Health Organization, 2019) diarrhea is an environmentally based and environmentally friendly disease. occurs in almost all geographical areas of the world. Every year there are around 1.7 billion cases of diarrhea with a death rate of 760,000 people. Objective: Aims to determine the educational benefits of administering electrolyte fluids (ORALIT) to treat dehydration in pediatric patients with GEDS (Moderate Diarrhea Gastroenteritis) in the Orchid Room at Bhakti Wira Tamtama Hospital, Semarang. Methods: The type of analysis that is used is quantitative analysis using a quasi-experimental one-group design for the pretest and posttest. It is the 30th week of the first trimester of the Islamic calendar. Purposive sampling is the method of sampling that is used.. Results: There is an effect of giving lemon aromatherapy to Emesis Gravidarum in First Trimester Pregnant Women. Conclusion: Lemon aromatherapy can reduce Emesis Gravidarum in first trimester pregnant women. Suggestion: Giving Lemon Aromatherapy to first trimester pregnant women.